Manajemen Pembelajaran Moral dan Keagamaan dalam Meningkatkan Karakter Anak Usia Dini di Taman Kanak-Kanak Kab. Bandung - Supyan Sauri; Deti Rostini; Siti Hassanah (Journal on Education, 2023)
The background of this research is the decline in moral and religious character in children, then coupled with a child's unfavorable environment, resulting in a decrease in character in children. The general purpose of this study was to find out the description of character improvement through moral and religious learning in early childhood in Pembina State Kindergarten and Al Kaustar Kindergarten, Bandung Regency. This research uses a qualitative approach through the case study method with observation, interviews and documentation studies. The results showed that: 1) The planning of moral and religious learning was prepared jointly by the head of the kindergarten, teachers, and some parents of students, set out in writing in the form of an Implementation Plan that refers to the 2013 PAUD curriculum, 2) The organization carried out was to form a team, namely the head of schools, teachers and parents and school stakeholders who design, develop programs and socialize to supervisors and parents of students, 3) The implementation of moral and religious learning includes opening activities, core activities and closing activities, in accordance with the required learning process standards, 4) Evaluation carried out found is to guarantee the achievement of predetermined basic competencies, check weaknesses in the implementation process, look for the causes of weaknesses and errors, find out the success of the program, diagnose and program improvement efforts, and be accountable to education stakeholders, 5) The obstacle is parents not playing an active role in helping schools realize and stimulate moral and religious learning at home, there are still many children who have not gotten used to moral and religious learning programs so that teachers must continue to be patient in getting used to every learning activity, 6) The solution is to involve teachers in training, explore various activities to improve children's character, provide education to parents about the importance of introducing various activities in improving children's character. The conclusion of this study is that the management of moral and religious learning in early childhood characters has been carried out in accordance with the provisions. In its implementation, it has implications for improving the character of early childhood.